Correction: Ferreira Lima dos Santos et al. Riding into Danger: Predictive Modeling for ATV-Related Injuries and Seasonal Patterns. Forecasting 2024, 6, 266–278 - Fernando Ferreira Lima dos Santos; Farzaneh Khorsandi; Guilherme De Moura Araujo (Forecasting)
Addition of an Author [...]